Miocene age of the Huanan basalt lava flow (NE China) inferred by reset of zircon (U–Th)/He thermochronometer in the underlying sand. Issue 11 (31st May 2020) - Zhou, Jianping; Dunkl, István; Liu, Yongjiang; Li, Weimin; Wolf, Anna; von Eynatten, Hilmar
Abstract : Mafic lavas of Cenozoic age are widely distributed in northeast China and received much attention as an important part of the Circum‐Pacific volcanic belt. The age constraints for the volcanic activity were determined mostly by K/Ar and 40 Ar/ 39 Ar methods. We present zircon (U–Th)/He ages obtained on the thermally overprinted sands directly underlying a basaltic lava. This thermochronometer is insensitive to weathering and not biased by excess argon, thus it can express accurately the age of thermal effect of the lava flow. As a regional cooling age reference, three granite samples were dated from basement units that have not been thermally influenced by the basalt eruptions. The reference granite samples revealed well‐defined Cretaceous (U–Th)/He‐ages, while 20 zircon crystals from the sand below the basalt lava revealed a prominent Miocene (U–Th)/He age component of 9.33 ± 0.24 Ma. Raman spectroscopy of these zircon crystals supports their thermally overprinted character. We infer that the sand sample has experienced significant thermal overprint by the overlying basalt lava leading to thermal reset of the majority of the detrital zircon crystals. The obtained age is thus interpreted as the eruption age of the basalt lava. The Huanan basalt flow thus belongs to volcanics of the Laoyeling episode in NE China.